Analysing splash in competitive diving - Driscoll, H.; Gaviria, S.; Goodwill, S. (Procedia Engineering, 2014)
Splash size is an important factor in competitive diving and is considered to have a large effect in final judged scores. The aim of this research was to develop a system to determine the splash size during different stages of the dive entry. One diver was recorded during a training session and their dives analysed using the developed system. Three splash metrics were calculated at time of complete entry and maximum splash: (1) width of splash, (2) height of splash and (3) size of splash. Results indicated that there was no relationship between the splash metrics at complete entry and time of maximum splash. This may have implications for the scoring of a dive if the judge is unable to distinguish between these two splash events.